Kampen om norsk politiutdanning - Aas, Geir (Tidsskrift for Professionsstudier, 2019)
The development of college degree for the Norwegian police education consists of a number of controversies and tensions, and this article discusses four key issues of contradictions in The Norwegian Police University College relatively short-lived history of 25 years. The demanding issues relate to the balance between breadth and depth in the education, short-term or long-term horizons for the training, the organization of the subjects in the curriculum and most of all the deviation of experience- versus scientific knowledge.